(untitled) (Research, Society and Development, 2022)
Erysipelas is defined as a cutaneous pathology and can be superficial or deep, affecting underlying lymphatic vessels, the main causative agent being the bacterium Streptococcus hemolyticus b. The objective was to report on the types of dressings used by nurses during the treatment of common and bullous erysipelas in an elderly patient during the hospitalization period. Descriptive, qualitative and retrospective study, of the experience report type. For data collection, the portfolios of the academics were used, where the events during the supervised internship period were reported daily. Different coatings such as fatty acids, collagenase, hydrogel and silver sulfadiazine were used for coatings at different times. Note the importance of other studies being developed and that health professionals, especially nurses, should go deeper into wound care, dressings and appropriate coverings for each type of wound.